Superhydrophobic Surfaces: Waterborne Fluorine‐Free Superhydrophobic Surfaces Exhibiting Simultaneous CO2 and Humidity Sorption (Adv. Mater. Interfaces 23/2019). Issue 23 (6th December 2019) - Baidya, Avijit; Yatheendran, Anagha; Ahuja, Tripti; Sudhakar, Chennu; Das, Sarit Kumar; Ras, Robin H. A.; Pradeep, Thalappil
Abstract : A waterborne, fluorine‐free, robust superhydrophobic material is developed from hydrophilic clay particles that capture moisture and CO2 simultaneously. While moisture and CO2 adsorption requires surfaces to be polar, superhydrophobicity needs them to be nonpolar. Both of these properties are controlled here by molecular functionalities of different dimensions. More details can be found in article number 1901013 by Avijit Baidya, Thalappil Pradeep, and co‐workers.